Contribution of King Manendra in the Developmemnt of Nepal - K C, Tej Bahadur (Academia Research Journal, 2023)
The presented study is limited to King Mahendra’s activities focused on the development of Nepal. From Prithvi Narayan Shah to Gyanendra Birvikram Shah, King Mahendra Birvikram Shah is a name that cannot be forgotten in the political history of Nepal and Nepali people even if they want to forget it. Although political parties and their leaders have accused King Mahendra of running the state in an autocratic style within the non-partisan governance system, of not being able to appreciate the sentiments of the people, and being stubborn, in fact, looking at the steps and decisions he took during his tenure, it seems that he is a person who understood the demands of the times and can address them. The main purpose of this study is to highlight the contribution of King Mahendra in the politics of Nepal. The conclusion of this article prepared on the basis of auxiliary sources is that the steps taken by King Mahendra with the intention of devoting himself to the country’s development and nationalism are considered to be in the interest of the nation.